The secret crusade eaudiobook - Bowden, Oliver (Assassin's Creed Origins, 2012)
Altaïr embarks on a formidable mission—one that takes him throughout the Holy Land and shows him the true meaning of the Assassin's Creed. To demonstrate his commitment, Altaïr must defeat nine deadly enemies, including Templar leader Robert de Sable. Here, for the first time, Niccolò Polo, father of Marco, shares Altaïr's remarkable story: his ongoing battle with the Templar conspiracy; a family life that is as tragic as it is shocking; the betrayal of an old friend; and a journey that will ultimately change the course of history.